Konsep dan Perkembangan Teori Maqasid - Agus Marimin (Jurnal Ilmiah Ekonomi Islam, 2022)
Maqâshid al-Syarî'ah are the ultimate goals that must be realized with the application of syar'at or Islamic law. The application of syar'at in real life (world), is to create the benefit or goodness of creatures on earth, which then has an impact on benefit or goodness in the hereafter. Excavation of benefits by the mujtahids, can be done through various methods of ijtihad. Basically, these methods lead to an effort to find "benefits", and make it a tool for establishing laws whose cases are not explicitly mentioned in the Qur'an or Sunnah. There are two methods of ijtihad developed by mujtahids in an effort to explore and determine benefits. The two methods are: First, the Ta'lîlî method (substantive analysis method) which includes Qiyâs and Istihsân. The two methods of Istishlâhî (Method of Benefit Analysis) which include Al-mashlahah al-Mursalah and al-dzarî'ah both sadd al-dzarî'ah and fath al-dzarî'ah categories.